Incidence and Clinical Risk of Cement Extravasation in Adult Patients Undergoing Prophylactic Vertebroplasty During Surgical Spine Reconstruction. (1st September 2019) - Bohl, Michael; Leveque, Jean-Christophe A; Sethi, Rajiv
Abstract: INTRODUCTION: Many have advocated for the use of prophylactic vertebroplasty in adult spinal reconstructions as a means of reducing complications related to poor bone quality, including proximal junctional kyphosis. Although numerous studies have evaluated the effectiveness of prophylactic vertebroplasty, none have evaluated safety. The purpose of this study was to measure the incidence and clinical severity of cement extravasation in adult patients undergoing prophylactic vertebroplasty as part of a spinal reconstruction procedure. METHODS: Consecutive adult patients treated with prophylactic vertebroplasty during a spinal reconstruction procedure were reviewed over a 46 mo time period. Spine reconstruction was defined as any procedure involving 6 or more levels of fusion or a 3-column osteotomy. Patients without postoperative computed tomography (CT) scan were excluded. Cement extravasation was graded using a novel grading system. Chi-square analyses and Fisher's exact tests were performed to identify independent predictors of cement extravasation. RESULTS: A total of 34 patients met the inclusion and exclusion criteria, comprising 112 vertebral bodies (VBs). All 34 patients (100%) had CT evidence of cement extravasation. In all 103 out of 112 VBs (92.0%) demonstrated cement extravasation and 13 VBs (11.6%) in 9 patients (26.5%) had cement extending to the vena cava, end-organs, or causing spinal canal stenosis. Upper thoracic vertebrae (C7-T6) had significantly higher rates of clinically worrisome extravasation than lower thoracic-lumbar (T7-L5) vertebrae ( P = .004). Two patients who underwent upper thoracic vertebroplasty suffered potentially devastating complications: one patient had an oxygen desaturation and a postoperative CT scan demonstrating cement in the heart and lungs. The second patient lost motor evoked potentials due to cement-induced spinal canal stenosis. No permanent clinical sequelae resulted from these events. CONCLUSION: Although no patients in this study suffered known long-term consequences of prophylactic vertebroplasty, 11.4% of patients had cement extravasation that threatened end-organs or neural elements. Upper thoracic vertebrae appear to pose a much higher risk for clinically dangerous cement extravasation.